Comparison of brown plant hopper in paddy field by using different trap method / Wan Muhammad Hasyimi Wan Hanipa - Wan Hanipa, Wan Muhammad Hasyimi (Faculty of Plantation and Agrotechnology, 2017)
A study about the population of Brown Plant Hopper (Nilaparvata lugens) at “Bendang Pergerakan Pemuda UMNO”, which is located in Tal Tujoh, Kelantan was done purposely to know the abundance of Brown Plant Hopper in paddy field and the comparison of effectiveness among the trap used which is Yellow Sticky Trap (YST) and Yellow Pan Trap (YPT). This study had been done for about six week, started from 26 July 2016 until 1 September 2016. The traps were setup randomly inside the plot near to paddy plot bed with one Yellow Sticky Trap and one Yellow Pan Trap for each point where the total traps are 12 Yellow Sticky Trap and 12 Yellow Pan Trap. Specimens of brown plant hopper were visualized manually at the field and collect the data twice a week starting from 1 August 2016. This study proved that the Yellow Sticky Trap was the most effective trap to collect the brown plant hopper compare to the Yellow Pan Trap where the YST collect 66% of the BPH collection compared to 34% by the Yellow Pan Trap. Besides that, the study shows that Brown Plant Hopper is not the major pest at the study field due to low population number.